Differences in physical activity according to mMRC grade in patients with COPD - Hayata, Atsushi (Int J Chron Obstruct Pulmon Dis, 2016)
BACKGROUND: Physical activity (PA) is impaired from the early stages of COPD, is associated with a worsening of disease prognosis, and causes COPD patients to restrict their daily activities in order to avoid breathlessness. The development of a simple tool to estimate physical activity level (PAL) could be useful for the management of COPD. OBJECTIVES: We investigated the differences in PA according to the modified Medical Research Council (mMRC) grade in patients with COPD. METHODS: A cross-sectional study was performed on stable outpatients with COPD. PA was measured for 2 weeks using a triaxial accelerometer, and dyspnea grade was evaluated in all patients using the mMRC scale. RESULTS: Ninety-eight patients were recruited. Significant differences in PA duration were observed at all intensities according to the mMRC grade. Despite treatment with controller medications, 59.2% of COPD patients had low PAL, which was <1.5 metabolic equivalents multiplied by hour per day. COPD patients with an mMRC grade ≥2, which was the most balanced cutoff point in the receiver operating characteristic curve, showed a higher reduction rate of PAL (80.0% at mMRC grade 2, 71.4% at mMRC grade 3, and 100% at mMRC grade 4). CONCLUSION: PA differed according to the mMRC grade, and mMRC grade ≥2 could predict a low PAL. Therefore, assessment of breathlessness by the mMRC questionnaire would be useful to stratify the risks of reduced PA in COPD.